The carcinogenic PAHs in breads, amount, analytical method and mitigation strategy, a systematic review study - Gholamreza Tavoosidana; Mansoreh Abdolhosseini; Yeghaneh Mazaheri; Burhan Basaran; Parisa Shavali-gilani; Parisa Sadighara (BMC, 2024)
Abstract Bread is one of the most consumed foods all over the world. Several contaminants are identified in bread. Polycyclic aromatic hydrocarbons (PAHs) is one of these contaminants. This systematic study evaluates the amount of four carcinogenic PAHs (PAH4) in various types of breads. To conduct this study, a comprehensive search was carried out using keywords of polycyclic aromatic hydrocarbons, PAHs, PAH4, and bread, with no time limitations. 17 articles were selected and fully evaluated. The observed range of PAH4 concentrations in bread varied from non-detected (ND) to 20.66 µg/kg. In the sample preparation process for analysis, an ultrasonic bath was predominantly utilized. Most chromatographic methods are able to measure PAHs in food, but the GC-MS method has been used more. To mitigate PAH levels in bread, it is suggested to incorporate antioxidants during the bread-making process. Furthermore, the type of bread, the type of fuel used to bake the bread, the temperature and the cooking time were some of the factors affecting the amount of PAH. Restricting these factors could significantly reduce PAH content. Regarding the risk assessment conducted in the manuscript, it was determined that industrial breads are usually considered safe. However, some traditional breads may pose risks in terms of their potential PAH content.